Bibliometric analysis of publication trends on ocular hygiene and infections in the past two decades - Ali, Mohsan; Naseer, Bisal; Insaf Ahmed, Rawal Alias; Talha, Muhammad; Saqib, Moeez; Anwar, Amar (German Medical Science GMS Publishing House, 2024)
Background: Ocular hygiene encompasses a spectrum of measures to initiate and maintain adequate ocular cleanliness to prevent eye infections and their further transmission. These infections affect all age groups and can lead to severe complications such as blindness. Nearly 1 billion cases could have been prevented out of over 2.2 billion people that are visually impaired worldwide. This bibliometric analysis focuses on the papers published on ocular hygiene and infections.Methods: We searched in the Scopus database from 2004 to 2024. After manual screening, a list of the 100 most-cited original articles was obtained, which was analysed for various factors, including temporal trends, subject areas, authorship patterns, country of origin, funding bodies, etc.Results: There has been a gradual decline over the past two decades in the number of publications. The United States was affiliated with the highest number of publications (n=61), followed by The United Kingdom (n=12) and Gambia (n=8). Several authors had 4 or more publications, with the highest number of publications by Rouse, B. T. (n=14). The American Journal of Ophthalmology takes the lead with 15 publications, while the National Eye Institute (n=23) was the leading funding body. Examination of institutional contributions shows that The University of Tennessee, Knoxville and UT College of Veterinary Medicine stand out with twelve publications each. Nearly half the publications belong to the field of medicine. However, significant publications also come from the fields Neuroscience, Microbiology and Immunology, Biochemistry, Genetics and Molecular Biology, etc. These findings highlight that there is great potential to conduct research to propagate ocular hygiene to prevent adverse effects of infections.